Biocontrol of plant diseases by bacillus subtilis : basic and practical applications - Shoda, Makoto (Boca Raton, Florida : CRC Press, 2019)
"Plant diseases are a serious threat to food production. This unique volume provides the fundamental knowledge and practical use of B.subtilis as a promising biocontrol agent. In order to replace chemical pesticides, one possibility is microbial pesticides using safe microbes. Bacillus subtilis is one of several candidates. Screening of the bacterium, the application of plant tests, clarification of its suppressive mechanism to plant pathogens and engineering aspects of suppressive peptides production are presented here. The author illustrates how B. subtilis is far more advantageous than, for example, Pseudomonas in biocontrol and can be considered as an useful candidate"--
2.8.1 Suppressive Effect by RB14 In Vitro (14)2.8.1.1 Materials and Methods; 2.8.1.2 Results; 2.8.2 Isolation of Iturin A and Surfactin from the Culture Broth of RB14; 2.8.2.1 Materials and Methods; 2.8.2.2 Results; 2.9 Characterization of B. subtilis YB8; 2.9.1 Production of Surfactin (22); 2.9.1.1 Methods and Results; 2.9.2 Production of Plipastatin; 2.9.2.1 Material and Methods; 2.9.2.2 Results; References; 3: In Vivo Plant Tests; 3.1 Biological Control of Crown and Root Rot and Bacterial Wilt (1); 3.1.1 Materials and Methods (1); 3.1.1.1 Bacterial Culture
OCLC-licensed vendor bibliographic record.
Keywords: Microbial pesticides; Bacillus subtilis -- Biotechnology; Phytopathogenic microorganisms -- Biological control; MEDICAL / Pharmacology; SCIENCE / Life Sciences / Botany; SCIENCE / Chemistry / General